Investigação experimental e modelo teórico para o índice de refração não-linear da linha D2 do césio - Araújo, Michelle Oliveira de (2013)
The response of a material to an incident radiation can be described in terms of the susceptibility of the medium. In an atomic vapor, this susceptibility strongly depends on the frequency of the radiation and can vary over several orders of magnitude near the resonance. When a material is illuminated by light whose electric field is intense, the Kerr effect may become significant, showing a linear variation of the refractive index as a function of the intensity of the laser beam. Several techniques allow the measurement of this nonlinear effect. One of the simplest and most accurate is the z-scan technique. It consists in moving the medium to be probed along the axis of a focused laser beam. The transmittance through an aperture is measured as a function of the cell position and the obtained curve allows one to determine the nonlinear refractive index (n2) of the material. In this work, we investigate the nonlinear refractive index of a vapor of cesium atoms. We used the z-scan technique for various detunings around the Cs D2 transition (wavelength at 852 nm). To monitor the frequency of the laser, we simultaneously used an auxiliary saturated absorption setup and a Fabry-Perot analyzer. Through simple relationships between n2 and the aperture transmittance, we obtained a value for n2 as a function of the laser detuning. A theoretical model was developed to be compared to our experimental results. We used the density matrix formalism to calculate n2, taking into account the velocity distribution of the atoms in the calculation of the matrix elements. We started by treating the atoms as two-level systems, which allows us to test different limits of velocity integration. We then carried out a more realistic model for the D2 line of Cs, considering one fundamental level and three excited levels. We showed that for each hyperfine transition, the third-order fundamental-excited coherence depends on the population of the excited states as well as on the coherence created between the excited levels. To our knowledge, our experimental results are the first measurements of n2 for a cesium vapor, using the z-scan technique. The measured values of n2 are consistent with our theoretical calculations.